Emergence and characteristics of multidrug-resistant Salmonella enterica subspecies enterica serovar Infantis harboring the pESI plasmid in chicken slaughterhouses in South Korea - Jiyeon Jeong; Myeongju Chae; Min-Su Kang; Ji-Youn Lee; Yong-Kuk Kwon; Hye-Jin Lee; So-Hee Lee; Hyeon-Bin Son; Jin-San Moon; Seongbeom Cho (Microbiology Spectrum)
ABSTRACT Salmonella enterica subsp. enterica serovar Infantis (S. Infantis), a major cause of human salmonellosis, is commonly associated with transmission via contaminated chicken meat. This study, as part of the national Salmonella monitoring program, assessed the prevalence of S. enterica, including S. Infantis, in chicken slaughterhouses across South Korea from 2014–2022. The presence of a megaplasmid, known as plasmid of emerging S. Infantis (pESI), was confirmed. This confirmation was based on multidrug-resistant and third-generation cephalosporin-resistant S. Infantis isolates using whole-genome sequencing. Phenotypic and genotypic characterization involved antimicrobial susceptibility tests, pulsed-field gel electrophoresis, polymerase chain reaction to screen for pESI plasmids, plasmid profiling, and conjugation assays. S. Infantis was identified in 9.3% of Salmonella-positive samples in 2014, undetected from 2015–2020, but re-emerged as the predominant serovar in 2021 (54.7%) and 2022 (75.5%). The isolates in 2014 were antibiotic susceptible, whereas most isolates from 2021 to 2022 exhibited multidrug-resistance, including resistance to third-generation cephalosporins. All isolates were sequence type 32 (ST32), with core genome multilocus sequence typing demonstrating pESI plasmid-based clustering. The pESI+ isolates harbored genes, such as aadA1, dfrA14, sul1, and tetA, and three multidrug-resistant pESI+ isolates harbored blaCTX-M-65. The plasmids were genetically similar to those observed in S. Infantis from broilers, chicken meat, and human clinical samples across various countries. This study highlights the spread of multidrug-resistant S. Infantis harboring the pESI plasmid with blaCTX-M-65 during early chicken production in South Korea. Continuous monitoring and control of resistant S. Infantis throughout the food chain is essential to inform public health initiatives.IMPORTANCEThis study highlights the critical emergence of multidrug-resistant (MDR) Salmonella enterica serovar Infantis (S. Infantis) in South Korea’s chicken slaughterhouses, driven by the acquisition of the pESI megaplasmid harboring the extended-spectrum beta-lactamase (ESBL) determinant blaCTX-M-65. Using whole-genome sequencing and comprehensive phenotypic-genotypic analyses, the findings reveal that pESI+ isolates in South Korea are genetically similar to strains from broilers, chicken meat, and human clinical cases worldwide. This underscores the transboundary nature of S. Infantis and its potential as a global public health threat.